How do you find critical points of multivariable function $f(x,y) = {x^3} + xy - {y^3}?$
Answer
Verified
444k+ views
Hint:First of all we will take the given expression and take differentiation with respect to “x” and “y” one by one and then find the factors and place the values of one variable to get the value for the other variable.
Complete step by step solution:
Take the given expression:
$f(x,y) = {x^3} + xy - {y^3}$
Differentiate the above expression with respect to “x”
\[\dfrac{d}{{dx}}f(x,y) = \dfrac{d}{{dx}}({x^3} + xy - {y^3})\]
Apply differentiation to all the terms on the right hand side of the equation inside the bracket.
\[{f_x} = \dfrac{d}{{dx}}({x^3}) + \dfrac{d}{{dx}}(xy) - \dfrac{d}{{dx}}({y^3})\]
Apply the formula in the above equation and place the value in it.
\[{f_x} = 3{x^2} + y\]
To find the critical value in the above equation equal to zero.
\[0 = 3{x^2} + y\] …. (A)
Similarly take derivative in the given expression with respect to “y”
\[\dfrac{d}{{dy}}f(x,y) = \dfrac{d}{{dy}}({x^3} + xy - {y^3})\]
Apply differentiation to all the terms on the right hand side of the equation inside the bracket.
\[{f_y} = \dfrac{d}{{dy}}({x^3}) + \dfrac{d}{{dy}}(xy) - \dfrac{d}{{dy}}({y^3})\]
Apply the formula in the above equation and place the value in it.
\[{f_y} = x - 3{y^2}\]
To find the critical value in the above equation equal to zero.
\[0 = x - 3{y^2}\] …. (B)
Take equation (A)
\[y = - 3{x^2}\]
Place the above value in the equation (B)
\[x - 3{( - 3{x^2})^2} = 0\]
Simplify the above equation-
\[x - 27{x^4} = 0\]
Finding the factors of the above equation.
$ \Rightarrow x(1 - 27{x^3}) = 0$
Implies
$x = 0$ …. (C)
or $1 - 27{x^3} = 0$
Simplify the above equation:
$1 = 27{x^3}$
When term multiplicative on one side is moved to the opposite side, then it goes to the
denominator.
$ \Rightarrow {x^3} = \dfrac{1}{{27}}$
Take a cube-root on both the sides of the equation.
$ \Rightarrow x = \dfrac{1}{3}$ …. (D)
Using the equation (C) and equation (A)
\[0 = 3{x^2} + y\]
Make “y” the subject, when any term is moved from one side to another the sign of the term also changes.
$y = - 3{x^2}$
Place $x = 0$
$ \Rightarrow y = - 3(0)$
Zero multiplied with anything gives zero.
$ \Rightarrow y = 0$ … (E)
Now, Place $x = \dfrac{1}{3}$ in equation (A)
$ \Rightarrow y = - \dfrac{1}{3}$
Hence, the critical points are: $(0,0)$ and $\left( {\dfrac{1}{3}, - \dfrac{1}{3}} \right)$
Note: Be careful about the sign convention when doing simplification. When you move any term from one side to another then the sign of the term also changes. Positive terms become negative and vice-versa.
Complete step by step solution:
Take the given expression:
$f(x,y) = {x^3} + xy - {y^3}$
Differentiate the above expression with respect to “x”
\[\dfrac{d}{{dx}}f(x,y) = \dfrac{d}{{dx}}({x^3} + xy - {y^3})\]
Apply differentiation to all the terms on the right hand side of the equation inside the bracket.
\[{f_x} = \dfrac{d}{{dx}}({x^3}) + \dfrac{d}{{dx}}(xy) - \dfrac{d}{{dx}}({y^3})\]
Apply the formula in the above equation and place the value in it.
\[{f_x} = 3{x^2} + y\]
To find the critical value in the above equation equal to zero.
\[0 = 3{x^2} + y\] …. (A)
Similarly take derivative in the given expression with respect to “y”
\[\dfrac{d}{{dy}}f(x,y) = \dfrac{d}{{dy}}({x^3} + xy - {y^3})\]
Apply differentiation to all the terms on the right hand side of the equation inside the bracket.
\[{f_y} = \dfrac{d}{{dy}}({x^3}) + \dfrac{d}{{dy}}(xy) - \dfrac{d}{{dy}}({y^3})\]
Apply the formula in the above equation and place the value in it.
\[{f_y} = x - 3{y^2}\]
To find the critical value in the above equation equal to zero.
\[0 = x - 3{y^2}\] …. (B)
Take equation (A)
\[y = - 3{x^2}\]
Place the above value in the equation (B)
\[x - 3{( - 3{x^2})^2} = 0\]
Simplify the above equation-
\[x - 27{x^4} = 0\]
Finding the factors of the above equation.
$ \Rightarrow x(1 - 27{x^3}) = 0$
Implies
$x = 0$ …. (C)
or $1 - 27{x^3} = 0$
Simplify the above equation:
$1 = 27{x^3}$
When term multiplicative on one side is moved to the opposite side, then it goes to the
denominator.
$ \Rightarrow {x^3} = \dfrac{1}{{27}}$
Take a cube-root on both the sides of the equation.
$ \Rightarrow x = \dfrac{1}{3}$ …. (D)
Using the equation (C) and equation (A)
\[0 = 3{x^2} + y\]
Make “y” the subject, when any term is moved from one side to another the sign of the term also changes.
$y = - 3{x^2}$
Place $x = 0$
$ \Rightarrow y = - 3(0)$
Zero multiplied with anything gives zero.
$ \Rightarrow y = 0$ … (E)
Now, Place $x = \dfrac{1}{3}$ in equation (A)
$ \Rightarrow y = - \dfrac{1}{3}$
Hence, the critical points are: $(0,0)$ and $\left( {\dfrac{1}{3}, - \dfrac{1}{3}} \right)$
Note: Be careful about the sign convention when doing simplification. When you move any term from one side to another then the sign of the term also changes. Positive terms become negative and vice-versa.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE